Prevention of loss in Mudarabah Sukuk Philosophical: Jurisprudence Study - Al-Ajami, Sawsan; Ghaith, Magdy (Jordan Journal of Islamic Studies, 2024)
The aim of this paper is to clarify the major reasons for losses, prevention methods, and ways to address them by employing a descriptive-analytical approach. The paper initially discusses the concept of loss and its types, and primarily focuses on the causes of loss in Mudarabah Sukuk and ways to prevent and address them. The results of the study suggest that trading in Sukuk is a type of liquidity management and hedges against losses and disperses risks. The paper also recommends the establishment of a market for Islamic securities and the development of a legislative framework to address losses and prevent the collapse of its institutions.